Innovative Changes in Education of the 2010s: Pro and Cons - Irina A. Kolesnikova (International Dialogues on Education: Past and Present, 2020)
The article offers a theoretical analysis of the advantages and contradictions of innovative changes in modern education. The author uses the data presented in the UNESCO and Council of Europe programmes, reviews in the main areas of innovative development, but also information from the websites of international organizations, implementing innovative educational models. The ideas of lifelong learning, inclusion and open education in the 2010s are meanwhile developing in conditions of "liquid modernity" (Bauman, 2000). Metamodern culture, the capitalization of knowledge, digitalization and network socialization are presented as the main external sources of the innovative boom in the education world of the 2010s. Against the background of the technological development one can see serious risks of forcing the humanitarian values and basic foundations out of pedagogic processes. In this regard, the need for constant critical reflection on the results of innovative education changes is emphasized.